Peran Strategis Lembaga Negara dalam Menegakkan Stabilitas Hukum dan Konstitusi di Negara Demokratis - Nova Marviana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
To maintain order the and continuity of democracy in Indonesia, legal and constitutional stability are essential. This article discusses the strategic functions of state institutions, including the executive, legislative, and judiciary, in ensuring the supremacy of law and constitutionalism. This paper investigates how cooperation between state institutions can strengthen a stable legal system that is responsive to socio-political changes using qualitative methodologies, such as desk studies and analysis of laws and regulations. This paper also emphasizes that state institutions face political pressure, regulatory inconsistencies, and interventions in the law enforcement process. This study offers policy suggestions to improve institutional capacity in maintaining legal and constitutional stability by comparing practices in other democratic countries. These study expected to help strengthennof Indonesian constitutional system to more than responsive to advances while maintaining the supremacy of law and democracy.